2021
DOI: 10.1115/1.4051747
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication, Mechanics, and Reliability Analysis for Three-Dimensional Printed Lattice Designs

Abstract: The use of 3D printing for lattice structures has led to advances in diverse applications benefitting from mechanically efficient designs. 3D printed lattices are often used to carry loads, however, printing defects and inconsistencies potentially hinder performance. Here, we investigate the design, fabrication, mechanics, and reliability of lattices with repeating cubic unit cells using probabilistic analysis. Lattices were designed with 500µm diameter beams and unit cell lengths from 0.8mm to 1.6mm. Lattices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Mechanics can also fluctuate due to manufacturing inconsistencies for the same design. Studies of DLP-printed lattices that tested 30 prints of the same design demonstrated a distribution of density and mechanical property measurements that occur due to fabrication inconsistencies [84]. The study investigated uncertainty and reliability for lattice mechanics and found that lattice failure due to yielding was highly affected by fluctuations in beam diameter.…”
Section: Testingmentioning
confidence: 99%
“…Mechanics can also fluctuate due to manufacturing inconsistencies for the same design. Studies of DLP-printed lattices that tested 30 prints of the same design demonstrated a distribution of density and mechanical property measurements that occur due to fabrication inconsistencies [84]. The study investigated uncertainty and reliability for lattice mechanics and found that lattice failure due to yielding was highly affected by fluctuations in beam diameter.…”
Section: Testingmentioning
confidence: 99%
“…Support material size was determined through preliminary testing to minimize support material to ensure its removal without destroying the surrounding structure while ensuring support material was printed large enough to facilitate structural stability during printing. Preliminary work and past studies informed these parameters as suitable limits for high-quality prints according to hardware constraints [41].…”
Section: Build Processmentioning
confidence: 99%
“…Polymers 2022, 14, x FOR PEER REVIEW 4 of 19 support material to ensure its removal without destroying the surrounding structure while ensuring support material was printed large enough to facilitate structural stability during printing. Preliminary work and past studies informed these parameters as suitable limits for high-quality prints according to hardware constraints [41]. Envision One Rapid Prototype software (EnvisionTec, Dearborn, MI, USA, version: 1.23.4820) was used to prepare digital files from STLs and add support material structure.…”
Section: Build Processmentioning
confidence: 99%
See 1 more Smart Citation